Penerapan inkubasi teknologi dan bisnis industri galangan kapal berbasis teknologi kayu komposit untuk mendukung enterpreunership di kampus Universitas Riau - Imam Suprayogi; Aras Mulyadi; Alfian Alfian; Fakhri Fakhri; Hendro Ekwarso; Nurdin Nurdin; Sri Djuniati; Safridatul Audah (Unri Conference Series: Community Engagement, 2022)
The main purpose of community service is the application of Composite Wood Material Technology innovation to strengthen the structure of the 1 GT wooden hull to extend the service life of the ship to support river tourism transportation modes as a form of synergy in strengthening universities (PT) with the Industrial World Business World (DUDI). as a Business and Technology Incubation Pilot in Support of Entrepreneurship for Riau University Students. The approach method applied to community service is to conduct a Workshop between Universities, the Industrial World and Students with an educational pattern of providing material and practice in the shipbuilding industry through partnerships to manufacture a full-scale physical model of a 1 GT wooden fishing boat in the community shipbuilding industry owned by Mr. Rusdi at Simpang Gelombang, Sipungguk Village, Kuok District, Kampar Regency through the application of coating technology on wooden ship hull structures. The main result of community service proves that the application of composite wood material technology using fast-growing wood species for the construction of 1 GT community fishing boats has been applied to the wooden shipbuilding industry. The synergy of innovation and partnership between PT and DUDI is believed to encourage increased sustainability of ship life and the community's economy to support river tourism transportation modes and encourage the acceleration of the Entrepreneurship Program at the Riau University Campus.